Through my eyes: an autoethnography of a refugee’s student educational journey - Souriya, Samanta P. (Kansas State University, 2021)
The goal of this research was to take readers through the intricate lived experience of a refugee student, navigating the U.S. public school system. Refugee students have continued to fall through the cracks, escalating the educational achievement gap. By 2050, the trajectory of U.S. public schools has indicated that immigrant youth, which includes refugees, will be one third of the 100 million U.S. children (Passel, 2011). Yet, schools across the nation failed to provide adequate education for this growing student population. Educators and school systems are still ill equipped to deal with the educational challenges and needs of refugee students. They may not understand or relate to the cultural background, language, socioeconomic, traumatic experiences, or perspective of these students. This qualitative study used an autoethnography research design to describe, explore, and analyze the essence of my own experience as a refugee student navigating through a U.S. elementary and secondary public school system. The autoethnography study offered my voice and interpretation, both as a refugee student and as a ESOL/Newcomers teacher adapting to American public-school culture. Vignettes and responses were used to encourage readers to reflect, understand, and empathize with some aspects of the educational experience of refugee students. Memories that spanned forty years ago served as the primary data source, which I used to construct my vignettes. The autoethnography study used five tenets of Critical Race Theory (CRT) as a framework to discover, examine, interpret, and address its role in the experience of a refugee student in a U.S. public school. The five CRT tenets were: (1) permanence of racism; (2) intersectionality; (3) counter storytelling; and (4) commitment to social justice and change. These concepts were used to analyze and interpret my candid vignettes and self-reflective responses. The findings suggested that the issues of race, class, power, poverty, identity, and racism were pervasive in my educational journey. The data exposed both sublet and overt racism that I have experienced throughout my primary and secondary education. The concept of intersectionality was salient throughout the analyzation and interpretations of the vignettes. The findings emphasized that my refugee educational journey included other overlapping factors such as, poverty, gender, class, and bicultural identity that contributed greatly to my overall experience as a refugee student. The second objective of this autoethnography was to look inward within myself and reflect on how my own experience as a former refugee student influenced my interactions and teaching practices with my refugee students. As I analyzed and interpreted my self-reflective responses, the following themes emerged: (1) family unit; (2) negotiating identity; (3) poverty; and (4) high expectation. The study suggested that having a strong family unit did contribute to my ability to overcome educational challenges. The study also revealed my tendency to have higher expectations on the refugee student population in comparison to their other immigrant counterpart. The research study offered current refugee students and their families an authentic, narrative handbook to reflect on, relate to, and glean valuable insight. These vignettes also illustrated how teachers’ deficiencies in diverse cultural background and sensitivity contributed to the education challenges of a refugee student as documented in the study. Hence, it is important for teachers of refugee students to recognize that the social and educational interactions with this group of students is impacted by their own assumptions, perceptions, comfort, knowledge, and understanding of the refugee culture. This study served as a catalyst for more discovery, discussion, and reflection, which can provide readers a greater possibility for better cross-cultural sensitivity and thus, influencing the adjustment and accommodation in the curriculum and instructions of refugee students.
Keywords: Autoethnography; Refugee student; Refugee experience; Critical race theory; Education